Granular cell tumor in the inguinal canal: A case report and literature review (Journal of Medical Sciences, 2018)
Granular cell tumors (GCT) are rare soft tissue neoplasms that may be asymptomatic or may be presented as a slow growing nodule. The diagnosis is established on the basis of cytological and histopathological characteristics of the disease. We present a case of granular cell tumor in the right inguinal region misdiagnosed as inguinal hernia.Case report:A 49-year-old female presented with a tender firm swelling in the right inguinal, 3x3 cm, firm in consistency that was present for three years. The swelling was reducible and the cough impulse was positive. Laboratory investigations were normal. Blood analysis showed: WBC: 7000/ul, Hb 11.5 g/dl, PLT 245 k/l, ESR 12 mm Ist hour uea 14 mg/dl, Cre .9 mg/dl, FBS 89 mg/dl,  and urinalysis was normal. A clinical diagnosis of inguinal hernia and hydrocele of canal of Nuck was performed. Ultrasound examination suggested an inguinal hernia. At surgery, a cystic mass, suspected to be hydrocele of Knucke, was resected and sent for histopathology (Fig 1-4). Histopathogy revealed sections with thick fibrous cystic walls, lined by one cell layer of simple mesothelial epithelium with foci of squamous metaplasia without evidence of atypia.  The underlying stroma showed dense fibrohistiocytic reaction, along with many multinucleated foreign body giant cells. Unremarkable fragment of striated muscle was observed. There was no evidence of malignancy. The diagnosis was of a hernia sac associated with nodular histiocytic mesothelial hyperplasia.